2010
DOI: 10.1177/1079063210384276
|View full text |Cite
|
Sign up to set email alerts
|

Postrelease Specialization and Versatility in Sexual Offenders Referred for Civil Commitment

Abstract: Offense specialization and versatility has been explored previously in the prior criminal records of sexual offenders. The present study expanded these findings by examining offense specialization and versatility in the postrelease offending of a sample of sexual offenders referred for civil commitment and released. Criminal versatility (not limiting one's offending to sexual crime) both before and after commitment was the most commonly observed offending pattern in the sample. Specialist offenders (those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 44 publications
8
56
1
Order By: Relevance
“…30,31 Instead, the convicted sex offender is characterized by a more general pattern of antisocial behavior. 32 The current study was designed to improve on earlier research with a longer-term follow-up into the adulthood (mean age, 51 years) of individuals with documented cases of childhood sexual and physical abuse and neglect and matched control individuals. We hypothesized that compared with physically abused and neglected children and matched control individuals, those with documented histories of childhood sexual abuse are at greater risk for being arrested for a sex crime and committing a larger number of sex crimes, are younger at their first arrest for a sex crime, and are more likely to specialize in sex crimes.…”
mentioning
confidence: 99%
“…30,31 Instead, the convicted sex offender is characterized by a more general pattern of antisocial behavior. 32 The current study was designed to improve on earlier research with a longer-term follow-up into the adulthood (mean age, 51 years) of individuals with documented cases of childhood sexual and physical abuse and neglect and matched control individuals. We hypothesized that compared with physically abused and neglected children and matched control individuals, those with documented histories of childhood sexual abuse are at greater risk for being arrested for a sex crime and committing a larger number of sex crimes, are younger at their first arrest for a sex crime, and are more likely to specialize in sex crimes.…”
mentioning
confidence: 99%
“…Furthermore, current research suggests that sexual offenders rarely restrict their criminal activities to sexual offenses (Harris, Knight, Smallbone, & Dennison, 2011;Lussier, 2005). Moreover, CSA-W rated the probability that they would abuse another child in the future much higher than those CSA who did not work with children (these differences showed the highest effect sizes).…”
Section: Discussionmentioning
confidence: 76%
“…In one assessment, Rydberg, Grommon, Huebner, and Bynum () found that sex offenders with an offense conviction against a child victim experienced more residence mobility than other contact sex offenders in preresidency and postresidency restriction time periods. The challenge to the development of a targeted policy arises in how to identify a small group of offenders who specialize in child molestation and differentiate this population from the versatility observed among those convicted of sexual offenses (Harris, Knight, Smallbone, and Dennison, ; Harris, Mazerolle, and Knight, ). Even with knowledge of offense specialization, little research has examined systematically whether repeat child molesters use consistent strategies to gain access to victims (Leclerc, Proulx, and Beauregard, ).…”
Section: Resultsmentioning
confidence: 99%